In situ cardiac regeneration by using neuropeptide substance P and IGF-1C peptide eluting heart patches. Issue 5 (12th October 2018) - Shafiq, Muhammad; Zhang, Yue; Zhu, Dashuai; Zhao, Zongxian; Kim, Dong-Hwee; Kim, Soo Hyun; Kong, Deling
Abstract: Cardiovascular diseases cause huge socio-economic burden worldwide. Although a mammalian myocardium has its own limited healing capability, scaffold materials capable of releasing stem cell recruiting/engrafting factors may facilitate the regeneration of the infarcted myocardium. The aim of this research was to develop cardiac patches capable of simultaneously eluting substance P (SP) and insulin-like growth factor-1C (IGF-1C) peptide. Polycaprolactone/collagen type 1-based patches with or without SP and IGF-1C peptide were fabricated by co-electrospinning, which exhibited nanofibrous morphology. SP and IGF-1C/SP patches recruited significantly higher numbers of bone marrow-mesenchymal stem cells than that of the negative control and patch-only groups in vitro . The developed patches were transplanted in an infarcted myocardium for up to 14 days. Mice underwent left anterior descending artery ligation and received one of the following treatments: (i) sham, (ii) saline, (iii) patch-only, (iv) IGF-1C patch, (v) SP patch and (vi) IGF-1C/SP patch. SP and IGF-1C/SP patch-treated groups exhibited better heart function and attenuated adverse cardiac remodeling than that of the saline, patch-only and individual peptide containing cardiac patches. SP patch and IGF-1C/SP patch-treated groups also showed higher numbers of CD31-positive vessels and isolectin B4-positive capillaries than that of other groups. IGF-1C/SP-treated group also showed thicker left ventricular wall in comparison to the saline and patch-only groups. Moreover, IGF-1C/SP patches recruited significantly higher numbers of CD29-positive cells and showed less numbers of Tunel-positive cells compared with the other groups. These data suggest that SP and IGF-1C peptides may act synergistically for in situ tissue repair.